Shifts of growing‐season precipitation peaks decrease soil respiration in a semiarid grassland. (27th November 2017) - Ru, Jingyi; Zhou, Yaqiong; Hui, Dafeng; Zheng, Mengmei; Wan, Shiqiang
Abstract: Changing precipitation regimes could have profound influences on carbon (C) cycle in the biosphere. However, how soil C release from terrestrial ecosystems responds to changing seasonal distribution of precipitation remains unclear. A field experiment was conducted for 4 years (2013–2016) to examine the effects of altered precipitation distributions in the growing season on soil respiration in a temperate steppe in the Mongolian Plateau. Over the 4 years, both advanced and delayed precipitation peaks suppressed soil respiration, and the reductions mainly occurred in August. The decreased soil respiration could be primarily attributable to water stress and subsequently limited plant growth (community cover and belowground net primary productivity) and soil microbial activities in the middle growing season, suggesting that precipitation amount in the middle growing season is more important than that in the early, late, or whole growing seasons in regulating soil C release in grasslands. The observations of the additive effects of advanced and delayed precipitation peaks indicate semiarid grasslands will release less C through soil respiratory processes under the projected seasonal redistribution of precipitation in the future. Our findings highlight the potential role of intra‐annual redistribution of precipitation in regulating ecosystem C cycling in arid and semiarid regions. Abstract : This study examining the effects of altered precipitation distributions in the growing season on soil respiration in a temperate steppe in the Mongolian Plateau, and finding that both advanced and delayed precipitation peaks suppressed soil respiration. The observations suggest that precipitation amount in the middle growing season is more important than that in the early, late, or whole growing seasons in regulating soil C release in grasslands and highlight the potential role of intra‐annual redistribution of precipitation in regulating ecosystem C cycling in arid and semiarid regions.